2020
DOI: 10.1186/s12940-020-00674-y
|View full text |Cite
|
Sign up to set email alerts
|

The use of a bed with an insulating system of electromagnetic fields improves immune function, redox and inflammatory states, and decrease the rate of aging

Abstract: Background The immune system, as a homeostatic system, is an excellent marker of health and has also been proposed as an indicator of the rate of aging. The base of the age-related changes in the immune system, “immunosenescence”, is oxidative-inflammatory stress. Studies have shown that long-term exposure to electromagnetic fields (EMFs) produced by technology causes inhibitory effects on the immune response and increases oxidation. The aim of the present study was to investigate the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 48 publications
(75 reference statements)
2
10
0
Order By: Relevance
“…In fact, in order to maintain health, it is necessary to have adequate homeostatic regulators, such as the nervous, endocrine and immune systems, as well as their intercommunication [44]. In a previous study [39] it was already shown that the use of this bed for two months was able to improve immune function, as well as the oxidative and inflammatory state, all this followed by a rejuvenation of the biological age, that is, of the rate of aging of the individuals [43,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, in order to maintain health, it is necessary to have adequate homeostatic regulators, such as the nervous, endocrine and immune systems, as well as their intercommunication [44]. In a previous study [39] it was already shown that the use of this bed for two months was able to improve immune function, as well as the oxidative and inflammatory state, all this followed by a rejuvenation of the biological age, that is, of the rate of aging of the individuals [43,45].…”
Section: Discussionmentioning
confidence: 99%
“…Both sleep and stress are situations in which the three homeostatic systems work together [46], and they can be affected by EMFs [47][48][49][50]. Thus, the use of a bed with EMFs-isolation-and-drain system, which improves immune system function [39] can also do that with the neuroendocrine system. In fact, this has been observed in the present work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stem cell exhaustion is a consequence of the sum of several hallmarks of aging mentioned above and is likely one of the main culprits for the loss of tissue regenerative capacity, and consequently organismal aging. Examples of that loss have already been related to immunosenescence [114,115].…”
Section: Stem Cell Exhaustionmentioning
confidence: 98%
“…Cell phone radiation exposure for 1 hour per day for 30 days compromised the immune system of rats, resulting in a significant decrease in immunoglobulin levels, total leukocyte, lymphocyte, eosinophil and basophil counts; and a significant increase in neutrophil and monocyte counts [51]. Shielding from EMFs was found to significantly improve immune function and decrease inflammation in humans; lymphocyte NK (natural killer) cell activity increased by 30% after EMF exposure was reduced for two months [52]. In 2015, a significant discovery was made that the brain was directly connected to the immune system by lymphatic vessels [53], which would mean that the immune system can be affected directly by the brain and environmental influences that affect the brain, such as wireless radiation.…”
Section: Wireless Radiation Affects the Immune System Increases Oxidative Stress And Inflammationmentioning
confidence: 99%